Strengthening Capacity for Prostate Cancer Early Diagnosis in West Africa Amidst the COVID-19 Pandemic: A Realist Approach to Rethinking and Operationalizing the World Health Organization 2017 Guide to Cancer Early Diagnosis - Elochukwu Fortune Ezenwankwo; Daniel A. Nnate; Catherine Adebukola Oladoyinbo; Hassan Mohammed Dogo; Ademola Amos Idowu; Chimdimma Peace Onyeso; Chidiebere Ndukwe Ogo; Motolani Ogunsanya; Olufikayo Bamidele; Chukwudi A. Nnaji (Ubiquity Press, 2022)
Two years after SARS-CoV-2 (COVID-19) was declared a global public health emergency, the restoration, at least, to the pre-pandemic level of early diagnostic services for prostate cancer has remained enormously challenging for many health systems, worldwide. This is particularly true of West Africa as the region grapples also with the broader impacts of changing demographics and overly stretched healthcare systems. With the lingering COVID-19 crisis, it is likely that the current trend of late prostate cancer diagnosis in the region will worsen with a concomitant increase in the burden of the disease. There is, therefore, a compelling need for innovative and evidence-based solutions to de-escalate the current situation and forestall the collapse of existing structures supporting early prostate cancer diagnosis in the region. In this viewpoint, we make a case for the operationalization of the World Health Organization (WHO) guide to early cancer diagnosis to strengthen the capacity for early prostate cancer diagnosis in West Africa using a realist approach, drawing on participatory health research and evidence-based co-creation. Ultimately, we demonstrate the potential for developing COVID-19 responsive and context-specific models to optimize patient navigation/journey along the essential steps of the World Health Organization guide to early cancer diagnosis.